Anticoagulation methods used and role of antithrombin III level monitoring in children on continuous renal replacement therapy: an observational cross-sectional study - Fatina Ibrahim Fadel; Hafez Mahmoud Bazaraa; Shahira Kamal Anis; Noha Mahmoud Mohamed; Yosra Aboelnaga Fahmy (SpringerOpen, 2024)
Abstract Background In critically ill cases, CRRT is a renal replacement intervention. The most common reason why CRRT terminates prematurely (non-electively) is clotting in the extracorporeal circuit, more especially in the filter. Aim of work To determine the frequency of thrombotic and hemorrhage complications throughout CRRT, the role of antithrombin III level monitoring, the type of anticoagulation, and the dose and laboratory tests utilized to monitor it. Method The study was carried out on 58 children who were undergoing CRRT. The children underwent a comprehensive history-taking, assessment, CRRT prescription parameters and alterations, vascular access data, anticoagulation type, dose, and adjustment, as well as monitoring of antithrombin III levels. Furthermore, any extracorporeal circuit clotting or bleeding was documented. Results Of the 58 sessions that were examined, 25 (43.1%) resulted in filter clotting. The indication was cured in 16 cases (27.6%), 8 cases (13.8%) resulted in the patient's mortality, and 9 cases (15.5%) had life-threatening bleeding. The remaining 33 cases (56.9%) were not terminated with filter clotting. Forty-one (70.7%) of studied sessions used unfractionated heparin as anticoagulation, 22.4% used heparin-protamine, 5.2% was not anticoagulated, and one circuit (1.7%) was anticoagulated using regional citrate. Filter clotting incidence was significantly related to activated partial thromboplastin time (a PTT) value at the end of sessions (P value = 0.000), and platelets count after 4 h of session initiation (P value = 0.048). Antithrombin III levels pre-heparin infusion less than 80 were found in patients who received higher doses of a heparin bolus dose, median dose 35 (IQR 20-35), this relation is statistically significant (P value = 0.042). Conclusion In the 58 cases that were examined, the incidence of bleeding was 32.8%; however, 19% of the cases were not severe. The incidence of filter clotting was 43.1% in the study group. a PTT value at the end of sessions, and platelets count after 4 h could be predictors of thrombotic complications during CRRT, antithrombin III deficiency before sessions is a predictor of filter clotting.